Together is better: higher committed relationships increase life satisfaction and reduce loneliness - Mertens, Alica; Neubauer, Andreas B.; Voß, Andreas; Oetzbach, Carolin Felicia (Journal of happiness studies, 2018)
Recently, the term mingle was introduced for persons with an intimate relationship who do not define themselves as romantic partners. This study examines differences between single, mingle and partnered adults in terms of life satisfaction and loneliness. Furthermore, need fulfillment is investigated as a mediator concerning the link between relationship status with life satisfaction and emotional loneliness. Lastly, a longitudinal analysis examined whether increases in commitment lead to higher well-being. A total of 764 participants completed an online questionnaire. Mingles fell in between singles and partnered adults regarding emotional loneliness and life satisfaction. With regard to female participants, relatedness and competence need fulfillment fully mediated the link between relationship status and life satisfaction whereas the association between relationship status and emotional loneliness was specifically mediated by the relatedness and autonomy component. Finally, shifting into more committed forms of relationship increased well-being regarding the longitudinal analysis.